SISTEM PENDUKUNG KEPUTUSAN UNTUK PROMOSI JABATAN MENGGUNAKAN METODE MOORA - Jamaludin Abdullah; Dony M Sihotang; Kornelis Letelay (Universitas Nusa Cendana, 2016)
Promote a position at a constitutes is one of important factor toemployee career planning also rejuvenatea position. DAMM PT.Surya Mustika's smoking distributor AMC'S Kupang always have Trouble in determine an employee to promoted the position.Spontaneous Supporting System application (SPK) Position promotion is designed to supportactivity in the officeso as the maker of decision will be take the decree which objective. In the position promotion process, anemployee will be evalutes by 10 criterions has been determined. The employee pontential evaluate will created a decisons the process used MOORA methode. The Result of this system count results ranking's alternative as recommendation for decision maker to be promoted. After done 4 examination time 10, 20, and 30 data test, then flowed by 5 data test to fire an examination employee already been promoted at period 2013 Marches 2015 to measure ranking's accuracies systems to ranking's that done by HRD used 10 that criterion, then obtainable ranking's result the same withthe percentage ofsuitabilityin the amount of 100%.